Transforming double absence into double presence.: Young migrants’ resistance to subordination: a case study in Barcellona Pozzo di Gotto and Milazzo (Sicily) - Bellinvia, Tindaro; Lo Schiavo, Lidia (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2024)
On the basis of the empirical findings of some ethnographic research, and drawing on Sayad’s concept of “double absence”, which is regarded as a pivotal key for the interpretation of the transnational nature of migrations, this paper heuristically introduces and discusses an alternative view. In fact, it aims to analytically reconstruct the practices put in place by young sub- Saharan migrants, including marriage, work and housing, instantiated both in their native and host countries, as a possible manifestation of their constant efforts to counter the alienating effects of “double absence”, by transforming it into “double presence”. The case-study forms part of an academic research programme which started in 2021 and is still ongoing; the ethnographic observations were carried out in Barcellona Pozzo di Gotto and Milazzo (Messina/Sicily) and include 45 qualitative interviews that were conducted from a longitudinal perspective.